Offensive zones in beach volleyball: differences by gender - Chinchilla-Mira, J. J.; Perez-Turpin, J. A.; Martinez-Carbonell, J. A.; Jove-Tossi, M. A. (Journal of Human Sport & Exercise, 2012)
The study was designed to develop a method for analysing on the offensive use of zones in the high competition, during the European Beach Volleyball Championships (2005), and (2006). And objective comparison of male and female playing characteristics is still missing in literature. We hypothesized that the gender differences in anthropometric and athletic properties (e.g. strength) as well as the different net heights (2.24 vs. 2.43 m) on the same field size (8x16 m) would be reflected in the game. Therefore, the aim of this study was to analyse the technical and tactical behaviour of female and male beach volleyball professionals and discover any gender differences. A quantitative analysis was carried out of 20 players (10 female and 10 male) taking part in the European Beach Volleyball Championship 2005 and 2006. Video recordings were made of the 659 points in eight matches played. The finished recordings were analysed using SPSS 17.0. The first significant result of the comparison showed that the mean most use of zones was in men (z1, z2, z4 and z5) in different for women was (z1 and z5). A second group of results showed the percentage the ball to the net was in men (7.73%) and in women (5.35%). Later analysis related that the ball out in men was (15.53%) and women was (27.38%). An understanding of the offensive use of zones are necessary for us to establish specific tactical training patterns for beach volleyball.